PENGARUH INTENSITAS PENGGUNAAN AI, LITERASI EKONOMI, DAN DUKUNGAN GURU TERHADAP KETERLIBATAN SISWA DENGAN EFIKASI DIRI SISWA SMAN 3 SEMARANG SEBAGAI VARIABEL MEDIASI - putri, Diankhoiriyani; Nina Oktarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effects of AI usage intensity, economic literacy, and teacher support on student engagement at SMAN 3 Semarang, with self-efficacy serving as a mediating variable. The study employs a non-experimental quantitative approach. The population consists of all 10th-grade students at SMAN 3 Semarang who are enrolled in economics courses, totaling 432 students. The sample comprises 208 respondents, determined using the Slovin formula and proportional sampling technique. The findings indicate that the intensity of AI usage does not significantly affect self-efficacy, whereas economic literacy and teacher support have a significant effect on self-efficacy. Furthermore, AI usage intensity, economic literacy, and teacher support significantly influence student engagement. However, AI usage intensity and economic literacy, when mediated by self-efficacy, do not have a significant effect on student engagement, while teacher support, through self-efficacy, has a significant effect on student engagement.